1996
DOI: 10.1074/jbc.271.16.9573
|View full text |Cite
|
Sign up to set email alerts
|

Two Pathways for Base Excision Repair in Mammalian Cells

Abstract: Abasic sites (apurinic/apyrimidinic, AP sites) are the most common DNA lesions generated by both spontaneous and induced base loss. In a previous study we have shown that circular plasmid molecules containing multiple AP sites are efficiently repaired by Chinese hamster extracts in an in vitro repair assay. An average patch size of 6.6 nucleotides for a single AP site was calculated. To define the exact repair patch, a circular DNA duplex with a single AP site was constructed. The repair synthesis carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
360
0
5

Year Published

1998
1998
2000
2000

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 481 publications
(384 citation statements)
references
References 22 publications
9
360
0
5
Order By: Relevance
“…We have previously shown that the short-patch BER in wild-type cell extracts is PCNA-independent (Frosina et al, 1996) and in Pol b-de®cient cells is slightly stimulated by PCNA (Fortini et al, 1998). The repair e ciency of Pol d-and Pol e-containing fractions was investigated in the presence of increasing amounts of PCNA (Figure 4).…”
Section: Characterization Of the Pol D And Pol E-containing Fractionsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that the short-patch BER in wild-type cell extracts is PCNA-independent (Frosina et al, 1996) and in Pol b-de®cient cells is slightly stimulated by PCNA (Fortini et al, 1998). The repair e ciency of Pol d-and Pol e-containing fractions was investigated in the presence of increasing amounts of PCNA (Figure 4).…”
Section: Characterization Of the Pol D And Pol E-containing Fractionsmentioning
confidence: 99%
“…The incorporation of radiolabeled dTMP in the BamHI ± HindIII restriction fragment marks mainly the occurrence of one-gap ®lling reactions that are the major route for repair of AP sites, while the incorporation of dCMP identi®es exclusively 2-6 nucleotides repair patches. Moreover since PCNA is required for the long-patch but not for the short-patch BER (Frosina et al, 1996;Fortini et al, 1998) the dependence of the repair reaction on this auxiliary protein is an additional marker to discriminate between the two pathways.…”
Section: Characterization Of the Pol D And Pol E-containing Fractionsmentioning
confidence: 99%
See 3 more Smart Citations